Resin composition, resin coating material, insulated wire, automobile wiring harness, and method for producing insulated wire for automobile wiring harness
By using a combination of ethylene-vinyl acetate copolymer resin with specific antioxidant and flame retardant, a resin composition that is crosslinked by electron rays is formed, which solves the problem of insufficient heat resistance and pass linearity of insulated wires in high temperature environments, and achieves excellent performance of heat resistance, crosslinking and pass linearity of insulated wires.
Patent Information
- Application Number
- CN202280006836.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-11-30
- Filing Date
- 2022-11-28
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-11-28
AI Technical Summary
It is difficult for existing insulated wires to maintain heat resistance and pass linearity in high temperature environments, and the crosslinkability of their insulated coatings is insufficient, which affects the overall performance of the wires.
An ethylene-vinyl acetate copolymer resin is used as the base resin, and an imidazole compound, a phenolic compound and a sulfide compound in a specific proportion are combined, and a bromine compound and an antimony compound are added to form a resin composition. The resin composition is crosslinked by electron rays to form an insulated electric wire with excellent heat resistance, crosslinkability and linearity.
It realizes excellent heat resistance and linearity of insulated wires in high temperature environments, ensures high crosslinking of the insulated coating, and improves the overall performance of automotive wiring harnesses.
Smart Images

Figure BDA0004165809320000181 
Figure BDA0004165809320000191
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a resin coating material, an insulated electric wire, an automobile wiring harness, and a method for producing the insulated electric wire for an automobile wiring harness. Background Art
[0002] Insulated wires with flame retardancy are widely used in various white appliances, OA equipment, etc. In addition, insulated wires used in automobiles, etc. are also required to have various properties such as flame retardancy or heat resistance, softness (flexibility), and mechanical properties. To date, many resin compositions have been studied and reported for achieving insulated wires with flame retardancy or heat resistance, softness (flexibility), and mechanical properties by using them as a covering material for conductors.
[0003] As a resin composition constituting an insulated wire having such desired characteristics, resins such as polyethylene and ethylene-vinyl acetate copolymer are widely used.
[0004] For example, Patent Document 1 discloses the following: by preparing a resin composition containing specific amounts of ethylene-vinyl acetate copolymer, specific flame retardant, specific multiple anti-aging agents, copper inhibitor and cross-linking aid, the composition is not easy to adhere to the processing machine (excellent processing adhesion) during the preparation of the resin composition, and the residual amount of the composition in the processing machine can be suppressed; in addition, by applying to the surface of a conductor and cross-linking, an insulated wire showing desired excellent properties in all aspects of flexibility, hardness, degree of cross-linking, abrasion resistance, flame retardancy, cold resistance and heat resistance can be obtained. The resin composition contains 15 to 30 parts by mass of a brominated flame retardant, 5 to 15 parts by mass of antimony trioxide, 6 to 12 parts by mass of a benzimidazole anti-aging agent, 2 to 4 parts by mass of a phenol anti-aging agent, 2 to 4 parts by mass of a thioether anti-aging agent, 0.5 to 2 parts by mass of a copper inhibitor, and 3 to 6 parts by mass of a cross-linking aid relative to 90 to 100 parts by mass of ethylene-vinyl acetate copolymer.
[0005] In addition, Patent Document 2 describes a flame-retardant resin composition, which, by using it as a conductor coating material, can obtain an insulated wire having excellent heat resistance life, flame retardancy, and coexistence with polyvinyl chloride (PVC), and does not cause the dissolution of heavy metal compounds and the generation of a large amount of smoke and corrosive gas when discarded by landfill, incineration, etc. The flame-retardant resin composition contains 50 to 160 parts by mass of a metal hydrate, 2 to 10 parts by mass of a phenolic antioxidant, 10 to 25 parts by mass of a benzimidazole antioxidant, and 0 to 10 parts by mass of a thioether antioxidant, relative to 100 parts by mass of an ethylene-vinyl acetate copolymer having a vinyl acetate content of 10% to less than 40% by mass or a mixture of an ethylene-vinyl acetate copolymer and a polyolefin.
[0006] In addition, Patent Document 3 describes an insulated wire having excellent flame retardancy, tensile properties, heat resistance and electrical properties, and does not generate elution of heavy metal compounds and a large amount of smoke and corrosive gas when disposed of in landfill, incineration, etc. The conductor of the insulated wire is coated with a crosslinked body of a composition, the composition containing 150 to 300 parts by mass of a metal hydrate, 1 to 6 parts by mass of a phenolic antioxidant and 12 to 30 parts by mass of a thioether antioxidant relative to 100 parts by mass of a base resin containing an ethylene-vinyl acetate copolymer, and the base resin has a vinyl acetate content of 40% or more.
[0007] In addition, Patent Document 4 describes a halogen-free flame-retardant wire / cable having excellent durability against corrosive gases such as NOx and SOx. The halogen-free flame-retardant wire / cable is characterized in that a halogen-free flame retardant is contained in an insulator or a sheath, and the insulator or the sheath is a composition in which 300 parts by weight or less of the halogen-free flame retardant is mixed with 100 parts by weight of rubber or plastic, and 0.1 to 10 parts by weight of a hindered phenol-based antioxidant and a thioether-based antioxidant are added respectively.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2019-14794
[0011] Patent Document 2: Japanese Patent Application Publication No. 2009-286903
[0012] Patent Document 3: Japanese Patent Application Publication No. 2002-42574
[0013] Patent Document 4: Japanese Patent Application Publication No. 2002-324442 Summary of the invention
[0014] Problems to be solved by the invention
[0015] With the development of hybrid vehicles in recent years, insulated wires used in automobiles are required to have better properties than before in terms of flexibility, hardness, degree of crosslinking, abrasion resistance, flame retardancy, cold resistance, and heat resistance. Regarding heat resistance, it is required to meet the requirements of heat resistance class 150°C of automobile standard (JASO) D624 (2015) or heat resistance class D of ISO 6722 (2006).
[0016] In addition, from the perspective of the end sealing properties of the insulated wire (preventing water from entering the connection part from the outside), it is known that the wire coating is compressed and deformed using rubber materials, etc. to ensure its water-stopping performance. In order to ensure such water-stopping performance, it is necessary to design the cross-linking degree (gel ratio) to be higher. In particular, in many resins, the heating deformation rate tends to increase under high temperature conditions. Under such conditions, if the insulation coating of the insulated wire is damaged (deformed), it may become the main reason for the damage to the sealing properties with the connector.
[0017] In addition, generally when processing or assembling wire harnesses, most of the wire harness processing such as cable end processing, connector insertion, and cable routing is performed manually. Especially when processing wire harnesses during periods when the surrounding environment changes significantly, such as summer, the linearity (slidability) between wire harness components and wires and cables or between wires is very important from the perspectives of work efficiency, the burden on operators, and assembly accuracy.
[0018] In view of the above, the present invention aims to provide a resin composition which, by using the resin composition to form an insulating film (resin coating material layer) of an insulated wire, can provide an insulated wire having excellent heat resistance, excellent crosslinking in the insulating film, and excellent linearity (easy sliding) between the obtained insulated wires under a high temperature environment. In addition, the present invention aims to provide a resin coating material using the resin composition, an insulated wire having the resin coating material around a conductor, an automotive wiring harness having the insulated wire, and a method for producing an insulated wire for an automotive wiring harness.
[0019] Means for solving problems
[0020] The present inventors have conducted intensive studies to solve the above problems and have found that, by using an ethylene-vinyl acetate copolymer resin as a base resin, blending specific amounts of an imidazole compound, a phenolic compound, and a thioether compound, and further blending specific amounts of a bromine compound and an antimony compound, the resin composition obtained can be used to form an insulating film of an insulated wire to provide an insulated wire having excellent heat resistance, high crosslinking properties, and excellent conductivity. The present invention has been completed based on these findings after further repeated studies.
[0021] That is, the above-mentioned problems are solved by the following means.
[0022] <1>
[0023] A resin composition comprising an ethylene-vinyl acetate copolymer resin as a resin component, wherein:
[0024] The resin composition contains an imidazole compound, a phenol compound and a thioether compound as antioxidants, and a bromine compound and an antimony compound as flame retardants.
[0025] Relative to 100 parts by mass of the total content of the above-mentioned resin components in the resin composition, the content of the above-mentioned imidazole compound is 14 parts by mass to 24 parts by mass, the content of the above-mentioned phenolic compound is 1.0 parts by mass to 2.0 parts by mass, the content of the above-mentioned sulfide compound is 0.3 parts by mass to 0.9 parts by mass, the content of the above-mentioned bromine compound is 15 parts by mass to 30 parts by mass, and the content of the above-mentioned antimony compound is 5 parts by mass to 15 parts by mass.
[0026] <2>
[0027] As mentioned above <1> The resin composition contains 0.5 to 6.0 parts by mass of a dispersant based on 100 parts by mass of the total content of the resin components in the resin composition.
[0028] <3>
[0029] As mentioned above <1> or <2> The resin composition comprises maleic acid-modified polyethylene resin and / or low-density polyethylene resin as the resin component.
[0030] <4>
[0031] As mentioned above <1> ~ <3> The resin composition described in any one of the preceding claims, wherein the ratio of the vinyl acetate component in the ethylene-vinyl acetate copolymer resin is 30% by mass or less.
[0032] <5>
[0033] As mentioned above <1> ~ <4> The resin composition described in any one of the preceding claims, wherein the total content of the antioxidant is 20 to 26 parts by mass based on 100 parts by mass of the total content of the resin components in the resin composition.
[0034] <6>
[0035] As mentioned above <1> ~ <5> The resin composition described in any one of the preceding claims, wherein the resin composition contains at least one of a cross-linking aid and a processing aid.
[0036] <7>
[0037] As mentioned above <1> ~ <6> The resin composition as described above is used for an automobile wire harness.
[0038] <8>
[0039] A resin-coated material, which is <1> ~ <7> Obtained by crosslinking any one of the resin compositions.
[0040] <9>
[0041] An insulated wire, wherein the insulating film has the above <8> The resin coating material.
[0042] <10>
[0043] A wiring harness for an automobile, which has the above <9> The insulated wire.
[0044] <11>
[0045] A method for manufacturing an insulated wire for automobile wiring harnesses, comprising the following steps: extruding a coating of the above-mentioned <1> ~ <7> A layer of the resin composition is formed by using any one of the resin compositions, and the layer of the resin composition is irradiated with electron beams of 80 kGy to 250 kGy.
[0046] In the present invention, a numerical range expressed using "to" means a range including the numerical values described before and after the "to" as a lower limit and an upper limit.
[0047] Effects of the Invention
[0048] The resin composition of the present invention can be used to form an insulating film (resin coating material layer) of an insulated wire to obtain an insulated wire having excellent heat resistance, excellent crosslinking in the insulating film, and excellent continuity between the obtained insulated wires. The resin coating material of the present invention can be used as a constituent material of the insulating film of an insulated wire to obtain an insulated wire showing the above-mentioned desired excellent characteristics. In the automotive wiring harness of the present invention, the insulated wire constituting the automotive wiring harness has the above-mentioned resin coating material in its insulating film, has excellent heat resistance, excellent crosslinking in the insulating film, and further excellent continuity under high temperature environment. According to the manufacturing method of the insulated wire used in the automotive wiring harness of the present invention, an insulated wire having the above-mentioned excellent characteristics can be obtained. DETAILED DESCRIPTION
[0049] [Resin composition]
[0050] The resin composition of the present invention contains specific amounts of ethylene-vinyl acetate copolymer resin as a base resin, imidazole compound, phenol compound, sulfide compound as antioxidants, and bromine compound and antimony compound as flame retardants.
[0051] The above-mentioned components and optional components described below may be used alone or in combination of two or more.
[0052] Hereinafter, each component contained in the resin composition of the present invention will be described.
[0053] <Ethylene-vinyl acetate copolymer resin>
[0054] The resin composition of the present invention contains at least ethylene-vinyl acetate copolymer resin as a resin component constituting a base resin. The polymerization form of the ethylene-vinyl acetate copolymer resin used in the present invention may be any of block, random and graft.
[0055] From the aspect of the closeness between the resin coating material and the conductor, and the linearity (easy sliding) between the wiring harness component and the electric wire or the electric wire, the content ratio of the vinyl acetate component constituting the above-mentioned ethylene-vinyl acetate copolymer is preferably 30% by mass or less, more preferably 25% by mass or less, and further preferably 20% by mass or less in the above-mentioned ethylene-vinyl acetate copolymer. In addition, from the same aspect as above, the content ratio of the vinyl acetate component is preferably 7% by mass or more, more preferably 9% by mass or more. In addition, by making the content ratio of the vinyl acetate component within the above-mentioned range, the resin coating material made using the resin composition of the present invention can obtain sufficient mechanical properties such as tensile strength and elongation at break, and in addition, the flame retardancy of the insulated wire can be further improved. It should be noted that the content ratio of the vinyl acetate component can be obtained, for example, by the mass ratio of the raw material (monomer) during synthesis.
[0056] The melt flow rate (MFR) of the ethylene-vinyl acetate copolymer resin used in the present invention is preferably 0.1 to 10 g / 10 min (load 2.16 kg, temperature 190° C.), more preferably 0.5 to 5 g / 10 min.
[0057] By making the melt flow rate of the ethylene-vinyl acetate copolymer resin within the above preferred range, the load on the kneading equipment or extruder can be further reduced when preparing the resin composition or making the insulated wire or wire harness, and the dispersibility of each component in the resin composition can be further improved. The melt flow rate (MFR) can be measured by a method based on JIS K 7210:2014.
[0058] The ethylene-vinyl acetate copolymer resin used in the present invention can be synthesized by a conventional method, or a commercial product can be used. Specific examples of commercial products include EVAFLEX V5274 and EVAFLEX V422 (both trade names) manufactured by Du Pont-Mitsui Polychemicals.
[0059] In the resin components constituting the resin composition of the present invention, the content of the ethylene-vinyl acetate copolymer resin is preferably 80% by mass or more, more preferably 85% by mass or more, and further preferably 90% by mass or more, from the perspective of improving flame retardancy and crosslinking properties. In addition, all the resin components contained in the resin composition of the present invention may be ethylene-vinyl acetate copolymer resins.
[0060] <Polyethylene resin>
[0061] In addition to the above-mentioned ethylene-vinyl acetate copolymer resin, the resin composition of the present invention may also contain polyethylene resin as a resin component other than the above-mentioned ethylene-vinyl acetate copolymer resin. As such polyethylene resin, for example, maleic acid-modified polyethylene resin, low-density polyethylene resin, etc. can be cited. Such polyethylene resin can be used alone or in combination of two or more. In the resin component constituting the resin composition of the present invention, the content of the polyethylene resin is preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 12% by mass or less, and may be 1% to 10% by mass, 2% to 8% by mass, or 3% to 5% by mass.
[0062] (Maleic acid modified polyethylene resin)
[0063] When the resin composition of the present invention contains a maleic acid-modified polyethylene resin component as a resin component, in the resin component constituting the resin composition of the present invention, the content of the maleic acid-modified polyethylene resin is preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 12% by mass or less, and may be 1% by mass to 10% by mass, 2% by mass to 8% by mass, or 3% by mass to 5% by mass. By making the content of the maleic acid-modified polyethylene resin within the above-mentioned preferred range, sufficient flexibility can be given to the insulated wire having the resin coated material made using the resin composition of the present invention. In addition, since the resin composition is difficult to fit with the processing machine (excellent processing adhesion), the residual amount of the composition in the processing machine can be suppressed. In addition, the compatibility of the resin component in the composition with the filler can be improved, and the wear resistance of the obtained insulated wire can be further improved.
[0064] (Low density polyethylene resin)
[0065] In the present invention, "low-density polyethylene resin" refers to a low-density polyethylene resin having a density of 0.929 g / cm 3 The following polyethylene resins: Therefore, the "low-density polyethylene resin" in the present invention includes "ultra-low-density polyethylene (VLDPE)" and the like in addition to "low-density polyethylene (LDPE)".
[0066] The preferred density range of the low-density polyethylene resin used in the present invention is 0.870 g / cm 3 ~0.929g / cm 3 , the more preferred density range is 0.910cm 3 ~0.929cm 3 It should be noted that the density of the polyethylene resin can be determined in accordance with JIS K7112:1999.
[0067] In addition, the low-density polyethylene resin may be, for example, a high-pressure free radical process (high-pressure process) low-density polyethylene resin or a metallocene catalyst linear low-density polyethylene resin. For details of such polyethylene resins, for example, reference may be made to the description of Japanese Patent Application No. 2016-072380.
[0068] When the resin composition of the present invention contains a low-density polyethylene resin as a resin component, in the resin component constituting the resin composition of the present invention, the content of the low-density polyethylene resin is preferably 20 mass % or less, more preferably 15 mass % or less, further preferably 12 mass % or less, and may be 1 mass % to 10 mass %, may be 2 mass % to 8 mass %, or may be 3 mass % to 5 mass %.
[0069] Polyethylene resins such as maleic acid-modified polyethylene resins and low-density polyethylene resins that can be used in the present invention can be synthesized by conventional methods, and commercial products can be used. Specific examples of commercial products include Petrothene 180R, Petrothene 170R, Petrothene 173R manufactured by Tosoh Corporation, Sumikathene F218-0, Sumikathene F200, Sumikathene G401 manufactured by Sumitomo Chemical Co., Ltd., NOVATEC UE320, NOVATEC LF443, NOVATEC LF280H, NOVATEC LF448K1, ADTEX L6100M manufactured by Japan Polyethylene Co., Ltd., NUC-9060, ENGAGE-8100 manufactured by NUC, and NUCG-5130 manufactured by Dow Elastomer (all trade names).
[0070] The total content of the resin components contained in the resin composition of the present invention is usually 30% by mass to 80% by mass, may be 40% by mass to 75% by mass, or may be 50% by mass to 75% by mass.
[0071] <Antioxidants>
[0072] The resin composition of the present invention contains specific amounts of an imidazole compound (imidazole antioxidant), a phenol compound (phenol antioxidant) and a thioether compound (thioether antioxidant) as antioxidants (anti-aging agents). By mixing specific amounts of these antioxidants, the occurrence of bleeding can be suppressed in the obtained resin coating material, and the heat resistance, crosslinking property and sliding property can be further improved.
[0073] The above antioxidants are described below.
[0074] (Imidazole compound)
[0075] Examples of the imidazole compound (compound having a benzimidazole skeleton) used in the resin composition of the present invention include 2-sulfanylbenzimidazole, 2-sulfanylmethylbenzimidazole, 4-sulfanylmethylbenzimidazole, 5-sulfanylmethylbenzimidazole and zinc salts thereof, and 2-sulfanylbenzimidazole and zinc salts thereof are preferred.
[0076] The present invention can use commercially available imidazole compounds, and examples of commercially available products include NOCRAC MBZ (trade name, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.).
[0077] The content of the imidazole compound is 14 to 24 parts by mass relative to 100 parts by mass of the total content of the resin components constituting the resin composition of the present invention. From the perspective of further improving heat resistance and crosslinking properties and suppressing dispersibility and bleeding in the resin, the content is preferably 16 to 24 parts by mass, and more preferably 16 to 20 parts by mass.
[0078] (Phenolic compounds)
[0079] The phenolic compound (compound having a phenol skeleton) used in the resin composition of the present invention includes, for example, triethylene glycol-bis(3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate), 1,6-hexanediol-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid, isooctyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and one or more thereof can be used. Among these, from the viewpoint of imparting high heat resistance to automotive wiring harnesses, those having two or more 3,5-di-tert-butyl-4-hydroxyphenyl groups or 3,5-di-tert-butyl-4-hydroxybenzyl groups are preferred, and 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid and pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) are particularly preferred. It should be noted that even compounds having a phenol skeleton (phenolic antioxidants) that are used as copper inhibitors in the form of triazole compounds, N,N'-diacylhydrazine compounds, or diacylhydrazine compounds as described later are not phenolic compounds in the present invention, but are treated as copper inhibitors.
[0080] In the present invention, commercially available phenolic compounds can be used. Examples of commercially available products include Irganox 1010 (trade name, manufactured by BASF) and ADK STAB AO-20 (trade name, manufactured by ADEKA).
[0081] The content of the phenolic compound is 1.0 to 2.0 parts by mass relative to 100 parts by mass of the total content of the resin components constituting the resin composition of the present invention. From the perspective of further improving heat resistance and crosslinking properties and inhibiting the occurrence of bleeding, the content is preferably 1.5 to 2.0 parts by mass.
[0082] (Thioether compound)
[0083] As the thioether compound (compound having a thioether bond) used in the resin composition of the present invention, there can be mentioned thioether compounds used as antioxidants for wire coating materials. For example, there can be mentioned dilauryl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, distearyl 3,3'-thiodipropionate, 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthiopropionate] (also known as bis[3-(dodecylthio)propionic acid] 2,2-bis[[3-(dodecylthio)-1-oxopropyloxy]methyl]-1,3-propanediyl), and the like, and one or more of them can be used. Among these, 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthiopropionate] is preferred from the viewpoint of long-term thermal stability.
[0084] The resin composition of the present invention can use a commercially available sulfide compound. Examples of commercially available products include ADK STAB AO-412S (trade name, manufactured by ADEKA Corporation).
[0085] The content of the above-mentioned sulfide compound is 0.3 to 0.9 parts by mass relative to 100 parts by mass of the total content of the resin component constituting the resin composition of the present invention. In the insulated wire having a resin composition highly mixed with sulfide compounds, the sulfide compounds are easy to seep out to the surface of the insulating film. When such an insulated wire is stored at high temperature, the sliding property is significantly impaired (the dynamic friction coefficient increases significantly), which will cause trouble for the assembly of the wire. Therefore, by making the content of the sulfide compound within the above range, a resin composition with excellent heat resistance and excellent sliding property can be obtained. From the perspective of further improving heat resistance, improving sliding property, and suppressing crosslinking hindrance, the content is preferably 0.3 to 0.6 parts by mass.
[0086] (Other antioxidants)
[0087] In addition to the above-mentioned imidazole compounds, phenolic compounds and thioether compounds, the resin composition of the present invention may also contain antioxidants other than these. As such antioxidants, for example, copper inhibitors and zinc compounds can be mentioned, and one or more of them can be used. As specific examples of zinc compounds, zinc sulfide and zinc oxide can be mentioned.
[0088] (Copper Inhibitors)
[0089] Examples of the copper inhibitor that can be used in the resin composition of the present invention include triazole compounds, N,N'-diacylhydrazine compounds, diacylhydrazine compounds, etc. Examples of commercially available products include heavy metal inertizing agents ADK STAB CDA series (CDA-1, CDA-6, CDA-10 (all trade names)) manufactured by ADEKA, and Irganox MD1024 (trade name) manufactured by BASF.
[0090] When the resin composition of the present invention contains a copper inhibitor, the content of the copper inhibitor is preferably 0.5 to 2.0 parts by mass based on 100 parts by mass of the total content of the resin components from the viewpoint of reduction in heat resistance due to contact with metal ions such as copper.
[0091] (Zinc Compounds)
[0092] As the zinc compound that can be used in the resin composition of the present invention, for example, zinc sulfide, zinc oxide, etc. can be cited. Among them, the resin composition of the present invention preferably contains zinc sulfide and / or zinc oxide. As commercial products of such zinc sulfide and zinc oxide, for example, SachtolithHD-S (trade name) manufactured by Sachtleben Chemie Gmbh company, Zinc sulfide manufactured by Taizhou ATS Optical Material company, etc. can be cited. It should be noted that in the present invention or this specification, the zinc compound does not include zinc salts of imidazole compounds used as imidazole compounds, and zinc stearate used as a processing aid (lubricant).
[0093] When the resin composition of the present invention contains a zinc compound, the content of the zinc compound is preferably 1.0 to 10 parts by mass, more preferably 3.0 to 5.0 parts by mass, based on 100 parts by mass of the total content of the resin component, from the viewpoint of heat resistance.
[0094] The total content of the antioxidant is preferably 10 to 35 parts by mass, more preferably 15 to 30 parts by mass, and even more preferably 20 to 26 parts by mass, based on 100 parts by mass of the total content of the resin components constituting the resin composition of the present invention.
[0095] <Flame retardant>
[0096] The resin composition of the present invention contains a bromine compound (bromine flame retardant) and an antimony compound (antimony flame retardant) as flame retardants. The ratio of the bromine compound to the antimony compound in the resin composition is preferably 2 to 5 times the molar amount of the bromine element per 1 mole of the antimony element.
[0097] The total content of the flame retardant in the resin composition of the present invention is preferably 20 to 45 parts by mass, more preferably 30 to 45 parts by mass, and even more preferably 31 to 42 parts by mass based on 100 parts by mass of the total content of the resin.
[0098] (Bromine compounds)
[0099] Examples of the bromine compound used as a flame retardant in the present invention include organic bromine-containing flame retardants such as brominated N,N'-ethylenebisphthalimide or compounds derived therefrom (these are collectively referred to as "brominated N,N'-ethylenebisphthalimide compounds"), N,N'-bis(bromophenyl)terephthalamide or compounds derived therefrom (these are collectively referred to as "N,N'-bis(bromophenyl)terephthalamide compounds"), brominated bisphenol or compounds derived therefrom (these are collectively referred to as "brominated bisphenol compounds"), and 1,2-bis(bromophenyl)alkane. Among these, for example, brominated N,N'-ethylenebisphthalimide and / or 1,2-bis(bromophenyl)ethane are preferably used.
[0100] As the bromine compound used in the resin composition of the present invention, a commercially available bromine compound can be used. Examples of commercially available products include SAYTEX 8010 (trade name, manufactured by Albemarle Corporation).
[0101] The content of the bromine compound in the resin composition of the present invention is 15 to 30 parts by mass based on 100 parts by mass of the total content of the resin components. From the viewpoint of flame retardancy, the content is preferably 20 to 30 parts by mass, and more preferably 24 to 30 parts by mass.
[0102] (Antimony compounds)
[0103] Antimony compounds include, for example, antimony trioxide, antimony tetroxide, antimony pentoxide, and sodium antimonate. It is believed that the reaction of antimony with chlorine (halogen) generates gases that shield oxygen, thereby promoting the formation of a carbonized layer and capturing free radicals (thermal decomposition chain reaction stops the action). Among them, antimony trioxide is preferably contained in the present invention from the perspective of forming a more stable carbonized layer.
[0104] In the present invention, commercially available antimony trioxide can be used. Examples of commercially available products include PATOX-C (trade name, manufactured by Nippon Seiko Co., Ltd.).
[0105] When the resin composition of the present invention contains an antimony compound, the content is 5 to 15 parts by mass relative to 100 parts by mass of the total content of the resin component. From the perspective of flame retardancy, the content is preferably 8 to 13 parts by mass, more preferably 9 to 12 parts by mass, and further preferably 10 to 12 parts by mass.
[0106] (Other flame retardants)
[0107] In addition to the above-mentioned bromine compounds and antimony compounds, the resin composition of the present invention may also contain a flame retardant that can be generally used in the insulating film of the insulated wire. As such a flame retardant, metal hydroxides (hydroxide-based flame retardants) such as magnesium hydroxide and aluminum hydroxide can be cited. When the resin composition of the present invention includes a hydroxide-based flame retardant, it is preferably less than 5 parts by mass, more preferably less than 3 parts by mass, relative to 100 parts by mass of the total content of the resin component.
[0108] <Other ingredients>
[0109] In addition to the above components, the resin composition of the present invention may contain other components such as the following crosslinking aids and processing aids within a range that does not impair the effects of the present invention. In addition, it may contain components such as plasticizers, fillers, and pigments as needed.
[0110] <Crosslinking aid>
[0111] The resin composition of the present invention also preferably contains a crosslinking aid. Examples of the crosslinking aid include polyfunctional compounds, preferably compounds having two or more (preferably three or more, more preferably 3 to 6) ethylenically unsaturated bonds (carbon-carbon double bonds) in the molecule.
[0112] Specific examples of the crosslinking aid include (meth)acrylate compounds such as polypropylene glycol di(meth)acrylate and trimethylolpropane tri(meth)acrylate, allyl compounds such as triallyl cyanurate, maleimide compounds, and divinyl compounds.
[0113] In the present invention, a commercially available crosslinking aid can be used. Examples of commercially available products include Ogmont T200 (trade name, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.).
[0114] The resin composition of the present invention preferably contains 2 to 6 parts by mass, more preferably 3 to 5 parts by mass, of a crosslinking aid based on 100 parts by mass of the total content of the resin components.
[0115] <Processing aids>
[0116] The resin composition of the present invention also preferably contains a processing aid. Preferred examples of the processing aid include metal soaps (lubricants).
[0117] Examples of the metal soap (lubricant) that can be used in the resin composition of the present invention include calcium stearate, zinc stearate, and magnesium stearate.
[0118] In the present invention, commercially available metal soaps can be used. Examples of commercially available metal soaps include SHINACA LEAD ZS-101 (trade name, manufactured by Shinagawa Chemical Industry Co., Ltd.).
[0119] When the resin composition of the present invention contains a lubricant, it is preferable that the lubricant is contained in an amount of 0.5 to 2 parts by mass based on 100 parts by mass of the total content of the resin components.
[0120] <Dispersant>
[0121] The resin composition of the present invention also preferably contains a dispersant. By containing a dispersant in the resin composition of the present invention, it is possible to prevent the re-agglomeration of additives such as flame retardants or antioxidants, improve the dispersibility of each component in the polymer, make the compound manufacturing process using a feeder extruder or a twin-screw extruder excellent, and further improve the heat resistance.
[0122] The dispersant that can be used in the present invention is not particularly limited, and a dispersant that is usually mixed into a resin composition can be used. From the aspect of further suppressing the re-agglomeration of the additive, the above-mentioned dispersant is preferably a wetting dispersant. A wetting dispersant refers to an additive that has both the function of a wetting material that acts as a surfactant to improve the wettability of the dispersoid to the resin component, and the function of preventing the dispersoid from agglomerating by effects such as electrical repulsion or steric hindrance. Usually, the function of the wetting material is assumed by a chain that is compatible with the resin component, and the function of preventing the dispersoid from agglomerating is assumed by an adsorptive group to the dispersoid. Commercially available products of wetting dispersants include, for example, BYK-MAX D4221 and BYK-MAXP4102 (both trade names, manufactured by BYK Chemical Japan Co., Ltd.).
[0123] When the resin composition of the present invention contains a dispersant, from the perspective of further improving heat resistance and suppressing the occurrence of blooming and crosslinking inhibition, the dispersant is preferably contained in an amount of 0.5 to 6.0 parts by mass, more preferably 1.0 to 6.0 parts by mass, relative to 100 parts by mass of the total content of the resin components.
[0124] <Additives>
[0125] The resin composition of the present invention may be appropriately blended with various additives such as ultraviolet absorbers, plasticizers, fillers, pigments, etc. as needed within a range not impairing the effects of the present invention.
[0126] [Method for producing resin composition]
[0127] The resin composition of the present invention can be obtained by blending the resin, antioxidant, flame retardant and other components, and the optional components as required, and melt-kneading them using a batch mixer such as a roll, kneader, Banbury mixer or a commonly used kneading device such as a twin-screw extruder.
[0128] [Insulated wire]
[0129] The insulated wire of the present invention has a layer of a resin coating material formed by crosslinking the resin composition of the present invention on the surface of the conductor (including a conductor bundle and a fiber core wire). It should be noted that the insulated wire of the present invention may have an intermediate layer or a shielding layer between the layer consisting of the conductor and the resin coating material.
[0130] The shape and material of the conductor may be any conductor as long as they are the shapes and materials used in the insulated wires generally used in the wiring harness for automobiles. The conductor may be a single wire or a stranded wire, and may be a bare wire or a tinned or enameled conductor. Examples of the metal material forming the conductor include soft copper, copper alloys, aluminum, and the like.
[0131] In addition, the thickness of the layer composed of the resin coating material formed around the conductor is not particularly limited, and is generally about 0.15 mm to 5 mm. When the resin composition of the present invention is used, there is the following advantage: even if the thickness of the resin coating layer is reduced, an insulated wire excellent in flexibility, hardness, crosslinking degree, flame retardancy, cold resistance and heat resistance can be obtained.
[0132] [Automotive wiring harness]
[0133] In the present invention or this specification, the automotive wiring harness is a general term for the wiring harnesses that are wired in various places of the vehicle such as the engine room, the dashboard, and the inside of the door according to environmental performance. The automotive wiring harness of the present invention has the insulated wire of the present invention. The resin composition of the present invention has excellent appearance and excellent flame retardancy and mechanical properties. Therefore, the wiring harness assembled with the insulated wire having a layer composed of a resin coating material formed by crosslinking the resin composition of the present invention can be suitably used for use in automobiles.
[0134] Hereinafter, the automotive wiring harness may be simply referred to as a "wiring harness".
[0135] [Method for producing insulated electric wire used in automotive wiring harness]
[0136] The insulated wire used in the automotive wiring harness of the present invention can be obtained by the following steps: extrusion coating the resin composition of the present invention on a conductor to form a layer of the resin composition, and irradiating the layer of the resin composition with electron beams of 80 kGy to 250 kGy. The electron beam irradiation causes a crosslinking reaction in the layer of the resin composition to form a resin coating material layer.
[0137] The crosslinking reaction by electron beam irradiation can be carried out by conventional methods and conditions. The electron beam irradiation conditions are preferably 80 kGy to 200 kGy, more preferably 80 kGy to 160 kGy. In addition, the acceleration voltage is preferably 300 keV to 3000 keV, more preferably 500 keV to 2500 keV.
[0138] In addition, a multilayer structure may be adopted in which an intermediate layer or a shielding layer is provided between the conductor and the coating layer or between the coating layers.
[0139] The conditions for extrusion molding the resin composition of the present invention are not particularly limited as long as the resin composition of the present invention can be extruded. From the perspective of reducing the load on the extruder (extrusion molding machine) and ensuring shape retention, the extrusion temperature (head) is preferably 100°C to 230°C, more preferably 120°C to 200°C.
[0140] In addition, other conditions of the extrusion molding can be appropriately set according to the purpose.
[0141] The screw structure of the extruder is not particularly limited, and a common full-flight screw, double-flight screw, front double-flight screw, Maddock screw, etc. can be used.
[0142] Example
[0143] The present invention will be described in more detail based on the following Examples and Comparative Examples, but the present invention is not limited to these Examples.
[0144] [Examples 1 to 13 and Comparative Examples 1 to 12]
[0145] The materials used to prepare the resin compositions of Examples 1 to 13 and Comparative Examples 1 to 12 are shown in Tables 1 and 2 below. The details of the materials used are as follows. It should be noted that (1) to (14) below correspond to (1) to (14) in Tables 1 and 2 below.
[0146] <Materials used>
[0147] (resin)
[0148] (1): Ethylene-vinyl acetate copolymer 1, EVAFLEX V5274 (trade name), content of vinyl acetate component: 17% by mass, manufactured by Du Pont-Mitsui Polychemicals
[0149] (2): Ethylene-vinyl acetate copolymer 2, EVAFLEX V422 (trade name), content of vinyl acetate component: 20% by mass, manufactured by Du Pont-Mitsui Polychemicals
[0150] (3): Maleic acid-modified polyethylene, ADTEX L6100M (trade name), manufactured by Japan Polyolefin Co., Ltd.
[0151] (4): Linear low-density polyethylene (LLDPE), NOVATEC UE320 (trade name), density 0.922 g / cm 3 、Manufactured by Japan Polyethylene Co., Ltd.
[0152] (Flame Retardant)
[0153] (5): 1,2-Bis(pentabromophenyl)ethane, SAYTEX 8010 (trade name), manufactured by Albemarle Corporation
[0154] (6): Antimony trioxide, PATOX-C (trade name), manufactured by Nippon Seiko Co., Ltd.
[0155] (Antioxidant)
[0156] (7): Zinc salt of 2-mercaptobenzimidazole, NOCRAC MBZ (trade name), manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0157] (8): Pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), Irganox 1010 (trade name), manufactured by BASF
[0158] (9): 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthiopropionate], ADK STAB AO-412S (trade name), manufactured by ADEKA Corporation
[0159] (10): 2',3-bis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl}propionohydrazide, Irganox MD1024 (trade name), manufactured by BASF
[0160] (11): Zinc sulfide, Sachtolith HD-S (trade name), manufactured by Sachtleben Chemie GmbH
[0161] (12): Zinc oxide, zinc oxide 2 types, manufactured by Mitsui Mining & Smelting Co., Ltd.
[0162] (Crosslinking aid)
[0163] (13): Trimethylolpropane trimethacrylate, Ogmont T200 (trade name), manufactured by Shin-Nakamura Chemical Industry Co., Ltd.
[0164] (Lubricant)
[0165] (14): Zinc stearate, SHINACA LEAD ZS-101 (trade name), manufactured by Shinagawa Chemical Co., Ltd.
[0166] (Dispersant)
[0167] (15): BYK-MAX D4221 (trade name), manufactured by BYK Chemicals Japan Ltd.
[0168] <Manufacturing of Resin Composition Sheet>
[0169] According to the compositions shown in Tables 1 and 2 below, the mixtures were melt-kneaded at 160° C. using a 1.7-liter Banbury mixer, and the resulting mixtures were molded into a sheet shape using a 6-inch roll mill.
[0170] Each of the obtained resin composition sheets was pressed into a thickness of 1 mm using a press machine set at a temperature of 160° C., and the pressed molded sheets were cross-linked using electron beams to obtain test samples (Examples 1 to 13, Comparative Examples 1 to 12). It should be noted that the cross-linking by electron beams was performed under the conditions of an acceleration voltage of 750 keV, 80 kGy, or 120 kGy.
[0171] [Performance evaluation]
[0172] Using each test sample produced as described above, the following performance evaluation was performed.
[0173] <Evaluation of Sliding Properties>
[0174] Using each test sample (Examples 1 to 13, Comparative Examples 1 to 12), the dynamic friction coefficient was measured under the following conditions in accordance with the method of JIS K 7125:1999.
[0175] Each test sample was cut into a length of 320 mm × width of 200 mm × thickness of 1 mm, and a 100 mm square low-density polyethylene sheet (model: UBEC130, manufactured by Ube Maruzen Polyethylene Co., Ltd.) was overlapped on it, and then a 100 mm square acrylic plate was overlapped on the low-density polyethylene sheet. A test load (30 N) was placed on the acrylic plate, and the low-density polyethylene sheet was stretched at a tensile speed of 100 mm / min. The friction force generated between each test sample and the low-density polyethylene sheet during the measurement distance of 80 mm was measured, and the dynamic friction coefficient (before heating) was calculated.
[0176] In addition, each test sample used in the measurement was heated at 50°C for 2 hours, and then allowed to stand until the temperature of each test sample reached room temperature, and the dynamic friction coefficient (after heating) was measured again under the same conditions. The ratio of the dynamic friction coefficient after heating to the dynamic friction coefficient before heating (dynamic friction coefficient after heating / dynamic friction coefficient before heating) was calculated from the obtained dynamic friction coefficient (before heating, after heating), and the obtained value was applied to the following evaluation criteria to evaluate the sliding property. A large value indicates that the sliding property is reduced due to heating.
[0177] -Evaluation Criteria-
[0178] A: less than 1.2
[0179] B: 1.2 or more and less than 1.5
[0180] C: 1.5 or above
[0181] <Crosslinking Evaluation>
[0182] Collect 0.1g of each test sample (Examples 1 to 13, Comparative Examples 1 to 12), use it as a specimen, and implement the test based on the method specified in Japan Automotive Engineering Society Standard (JASO) D618 6.14.2. Specifically, put the sample in a test tube, add 20ml of xylene, and heat it at 120°C for 24 hours. Then take out the sample, dry it in a dryer at 100°C for 6 hours, naturally cool it to room temperature (23°C), and then accurately weigh the mass. The percentage of the mass of the sample after xylene immersion ~ drying relative to the mass of the sample before xylene immersion ([mass of the sample after xylene immersion ~ drying / mass of the sample before xylene immersion] × 100) is taken as the gel fraction, and the following criteria are applied to evaluate the crosslinking property.
[0183] -Evaluation Criteria-
[0184] A: Gel rate is more than 70%
[0185] B: Gel fraction is 50% or more and less than 70%
[0186] C: Gel rate less than 50%
[0187] <Heat resistance evaluation>
[0188] Based on the method specified in the Japan Automotive Engineering Society Standard (JASO) D618, the heat resistance is evaluated by continuous heat resistance temperature. Specifically, each test sample (Examples 1 to 13, Comparative Examples 1 to 12) was punched into a dumbbell-shaped No. 3 type described in JIS K6251:2017 as a test piece, and an aging test was carried out at each temperature of 170°C, 180°C, 190°C, and 200°C. The time from the elongation at break to the state of fracture when the elongation at break is 100% (the state of 2 times elongation is 100%) is determined, and the temperature at which the state of fracture is reached when the elongation at break is set to 100% in 10,000 hours is determined from the Arrhenius curve, and is used as the heat resistance life temperature. The heat resistance life temperature is applied to the following criteria to evaluate the heat resistance.
[0189] -Evaluation Criteria-
[0190] A: Above 151℃
[0191] B: 150℃ or higher and less than 151℃
[0192] C: less than 150℃
[0193] The obtained results are summarized in Tables 1 and 2 below.
[0194]
[0195]
[0196]
[0197] The content of each component in the table is in parts by mass. "-" means that the corresponding component is not included.
[0198] As can be seen from Table 2, the resin composition sheet using the resin composition that does not satisfy the requirements of the present invention is inferior in at least one of the evaluation items of sliding property, crosslinking property, and heat resistance.
[0199] In contrast, the resin composition sheet produced using the resin composition of the present invention was excellent in all evaluation items as shown in Table 1. This shows that the resin composition of the present invention can achieve excellent properties as a resin coating material layer of an automobile wire harness.
[0200] The present invention has been described in conjunction with its embodiments, but the applicant believes that, unless otherwise specified, the present invention is not limited to any details in the description and should be broadly interpreted without violating the spirit and scope of the invention as shown in the appended claims.
[0201] This application claims priority based on Japanese Patent Application No. 2021-194495 filed in Japan on November 30, 2021, the contents of which are incorporated herein by reference as a part of the contents described in this specification.
Claims
1. A resin composition comprising an ethylene-vinyl acetate copolymer resin as a resin component, wherein: The resin composition contains an imidazole compound, a phenol compound and a thioether compound as antioxidants, and a bromine compound and an antimony compound as flame retardants. Relative to 100 parts by mass of the total content of the resin component in the resin composition, the content of the imidazole compound is 14 parts by mass to 24 parts by mass, the content of the phenolic compound is 1.0 parts by mass to 2.0 parts by mass, the content of the sulfide compound is 0.3 parts by mass to 0.9 parts by mass, the content of the bromine compound is 15 parts by mass to 30 parts by mass, and the content of the antimony compound is 5 parts by mass to 15 parts by mass, In the resin component constituting the resin composition, the content of the ethylene-vinyl acetate copolymer resin is 80% by mass or more.
2. The resin composition according to claim 1, wherein The resin composition contains 0.5 to 6.0 parts by mass of a dispersant based on 100 parts by mass of the total content of the resin components in the resin composition.
3. The resin composition according to claim 1 or 2, comprising a maleic acid-modified polyethylene resin and / or a low-density polyethylene resin as the resin component.
4. The resin composition according to claim 1 or 2, wherein The ratio of the vinyl acetate component in the ethylene-vinyl acetate copolymer resin is 30% by mass or less.
5. The resin composition according to claim 1 or 2, wherein The total content of the antioxidant is 20 to 26 parts by mass based on 100 parts by mass of the total content of the resin components in the resin composition.
6. The resin composition according to claim 1 or 2, wherein The resin composition contains at least one of a cross-linking aid and a processing aid.
7. The resin composition according to claim 1 or 2, which is used for an automobile wiring harness. 8 . A resin-coated material obtained by crosslinking the resin composition according to claim 1 .
9. An insulated wire, wherein: The insulating film comprises the resin coating material according to claim 8 . 10 . An automobile wiring harness comprising the insulated electric wire according to claim 9 .
11. A method for producing an insulated wire for automobile wiring harness, comprising the steps of: extrusion coating a conductor with the resin composition according to any one of claims 1 to 7 to form a layer of the resin composition, and irradiating the layer of the resin composition with electron beams of 80 kGy to 250 kGy.
Citation Information
Patent Citations
Insulated wire
JP2002042574A
Halogen-free flame-retardant electric wire / Cable
JP2002324442A
Flame-retardant resin composition and electric wire coated therewith
JP2009286903A
Semiconductor or electronic component mounting device and semiconductor or electronic component mounting method
JP2016072380A
Resin composition, resin coating material, wire harness for automobile and method for manufacturing wire harness for automobile
JP2019014794A